Réponses

2012-09-16T14:27:52+02:00

c'est résoudre je suppose ?

 

1)(3x-4)^2=100      

(3x-4)^2-100 = 0 (3x-4)^2-10² = 0 (3x - 4 - 10)(3x - 4 + 10) = 0 (3x - 14)(3x + 6) = 0 3(3x - 14)(x + 2) = 0   2 solutions : x = -14/3 ou x = -2       

 

2) (2x+7)^2=1

(2x+7)^2 - 1² = 0

(2x+7-1)(2x+7+1) = 0

(2x+6)(2x+8) = 0

4(x+3)(x+4) = 0

 

2 solutions : x = -3 ou x = -4

 

3) (x-1)^2=(x-7)^2        

(x-1)^2 - (x-7)^2 = 0 (x - 1 - x + 7)(x - 1 + x - 7) = 0 8(2x - 8) = 0 16(x - 4) = 0   1 seul solution : x = 4

 

4) (3x-2)^2=x^2

(3x-2)^2 - x^2 = 0

(3x - 2 -x) (3x - 2 +x) = 0

(2x - 2)(4x - 2) = 0

4(x-1)(2x - 1) = 0

 

2 solutions : x = 1 ou x = 1/2

 

En espérant t'avoir aidé.